2008
DOI: 10.1111/j.1462-2920.2008.01728.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple bacterial symbionts in two species of co‐occurring gutless oligochaete worms from Mediterranean sea grass sediments

Abstract: Gutless oligochaete worms are found worldwide in the pore waters of marine sediments and live in symbiosis with chemoautotrophic sulfur-oxidizing bacteria. In the Mediterranean, two species of gutless oligochaete worms, Olavius algarvensis and O. ilvae, co-occur in sediments around sea grass beds. These sediments have extremely low sulfide concentrations (< 1 microM), raising the question if O. ilvae, as shown previously for O. algarvensis, also harbours sulfate-reducing symbionts that provide its sulfur-oxidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
66
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 37 publications
2
66
2
Order By: Relevance
“…Acidobacteria, a phylum that was found to be abundant in deep-sea Mediterranean waters (Quaiser et al, 2008), was also relatively well represented in mesopelagic waters, but not in deeper waters. By contrast, Acidobacteria were one of the three dominant groups in sediment libraries, together with Gamma-and mostly sulfate-reducing Delta-proteobacteria ( Figure S5; Woyke et al, 2006), relatives of which have been found in association with other gutless oligochaete worms in the Mediterranean (Ruehland et al, 2008). This suggests that some of the sediment-associated bacteria form stable endosymbiotic associations with a variety of anaerobic eukaryotic hosts.…”
Section: Resultsmentioning
confidence: 96%
“…Acidobacteria, a phylum that was found to be abundant in deep-sea Mediterranean waters (Quaiser et al, 2008), was also relatively well represented in mesopelagic waters, but not in deeper waters. By contrast, Acidobacteria were one of the three dominant groups in sediment libraries, together with Gamma-and mostly sulfate-reducing Delta-proteobacteria ( Figure S5; Woyke et al, 2006), relatives of which have been found in association with other gutless oligochaete worms in the Mediterranean (Ruehland et al, 2008). This suggests that some of the sediment-associated bacteria form stable endosymbiotic associations with a variety of anaerobic eukaryotic hosts.…”
Section: Resultsmentioning
confidence: 96%
“…Spirochetes, which are traditionally associated with marine sediments or microbial mats, were only detected at the core OMZ depths (110, 200 m), consistent with this group being dominated by strictly or facultatively anaerobic members (Munn, 2011). Marine spirochetes have also been found in association with eukaryotes (Ruehland et al, 2008;Demiri et al, 2009), and may therefore be enriched in the particle fraction via attachment to larger organisms or sinking fecal matter. Similarly, sequences matching Mollicutes, which here were affiliated exclusively with the Mycoplasma (data not shown), may have originated from eukaryotic material, as mycoplasmas have been found in the larval stages of marine invertebrates and in the intestinal microflora of several fish species (Zimmer and Woollacott, 1983;Bano et al, 2007).…”
Section: Oxygen Conditionsmentioning
confidence: 99%
“…O. algarvensis lives in coarse-grained coastal sediments off the island of Elba, Italy, and migrates between the upper oxidized and the lower reduced sediment layers (6). It hosts a stable and specific microbial consortium consisting of five bacterial endosymbionts in its body wall: two aerobic or denitrifying gammaproteobacterial sulfur oxidizers (γ1-and γ3-symbionts), two anaerobic deltaproteobacterial sulfate reducers (δ1-and δ4-symbionts), and a spirochete with an unknown metabolism (7,8). The sulfate-reducing δ-symbionts provide the sulfur-oxidizing γ-symbionts with reduced sulfur compounds as an internal energy source for autotrophic CO 2 fixation via the Calvin-Benson cycle, thus explaining how O. algarvensis can thrive in its sulfide-poor environment (6, 9).…”
mentioning
confidence: 99%